2009
DOI: 10.1590/s1984-82502009000300008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antinociceptive and anti-inflammatory effects of the acetone extract from Anacardium occidentale L

Abstract: The stem bark of Anacardium occidentale L. (Anacardiaceae), commonly called cashew, is used in Brazilian traditional medicine for the treatment of gastric and inflammatory disorders. The present study was carried out to investigate the in vivo anti-inflammatory activities of the acetone extract (AE) of the stem bark of A. occidentale. We evaluated the pharmacological activities of this plant material through the analgesic, antiedematogenic and chemotaxic inhibitory effects produced by the AE. The oral administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 14 publications
2
8
0
5
Order By: Relevance
“…A similar activity was observed with the hydroethanolic extract of cashew leaves, where tannins were suggested as being responsible for moieties (Konan and Bacchi, 2007). Vanderlinde et al (2009) reported that the acetone extract of cashew stem bark in rodents contains antibodies, and has anti-inflammatory and antinociceptive effects. The dichloromethane extract of cashew leaves is also suggested to have an analgesic effect on rats (Onasanwo et al, 2012).…”
Section: A Occidentale and Its Biological Rolessupporting
confidence: 69%
“…A similar activity was observed with the hydroethanolic extract of cashew leaves, where tannins were suggested as being responsible for moieties (Konan and Bacchi, 2007). Vanderlinde et al (2009) reported that the acetone extract of cashew stem bark in rodents contains antibodies, and has anti-inflammatory and antinociceptive effects. The dichloromethane extract of cashew leaves is also suggested to have an analgesic effect on rats (Onasanwo et al, 2012).…”
Section: A Occidentale and Its Biological Rolessupporting
confidence: 69%
“…The pain caused by the injection of the latter is due to the release of serotonin, histamine, bradykinin, and prostaglandins (PGEβα, PGFβα). These mediators induce stimulation of peripheral neurons and then induce an increase in vascular permeability [19,26]. The foliar extract of the studied plant significantly inhibited abdominal torsion in a dosedependent manner.…”
Section: Analgesic Activitymentioning
confidence: 96%
“…More specifically, the anti-inflammatory and cicatrizing effects from the aqueous extract of A. occidentale were shown by the clinical evaluation of patients with skin injury or mucosa lesions such as oral or vulva erosion, uterus inflammation and body ulceration (Lopes et al, 2003). Several further investigations were carried out to determine possible mechanisms involved in antiinflammatory properties from A. occidentale (Olajide et al, 2004;Vanderlinde et al, 2009).…”
Section: Anadenanthera Colubrina (Vell) Brenan Fabaceae (Angico-bramentioning
confidence: 99%